Improve secure based multi-path routing to mitigate the intrusion endurance in heterogeneous wireless sensor networks - G. Murugan, Dr. (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks (WSNs) have many potential applications. Multi-path routing is widely used in WSN to achieve reliability and perform Fault Tolerance. Multi-path routing determines and assigns multiple routes from a given sensor node to the sink. The transmission of data among the multi-path brings path redundancy, which increases the reliability and reduces the network congestion. In this research work, a dynamic redundancy management algorithm is proposed. To exploit multi-path routing in order to process the user request with existence of defective and malicious nodes. The objective of this work is to analyze the trade-off between energy consumption and Quality of Service (QoS) gain in security and reliability in order to increase the lifetime. The optimized redundancy level of multipath routing is determined dynamically which is used to improve the query response while extending the network lifetime and also for detecting intrusions and send alert to the system through Intrusion Detection System (IDS). Then, a voting-based distributed Intrusion Detection (ID) algorithm is proposed to detect and remove malicious nodes in a sensor network. The malicious node has been determined through number of voters using voting-based distributed ID algorithm. The efficient redundancy management of a clustered Heterogeneous Wireless Sensor Network (HWSN) is to increase the network lifetime in the presence of unreliable and malicious nodes. Therefore, the reliability improved dramatically.Â Â